2021
DOI: 10.3389/fpls.2021.679629
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Resistance to Fusarium Wilt in Mung Bean (Vigna radiata L.)

Abstract: Fusarium wilt is a destructive soil-borne disease that threatens the production of mung bean. Mung bean lines Zheng8-4 and Zheng8-20 show high resistance and high susceptibility to Fusarium wilt, respectively. Transcriptome analysis was carried out to identify candidate genes involved in Fusarium wilt resistance using Zheng8-4 and Zheng8-20 at 0, 0.5, 1, 2, and 4 days post inoculation (dpi). Differential expression analysis showed that 3,254 genes responded to pathogen infection and were differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Pathogen invasion is known to affect the structure and integrity of the plant cell wall. In this study, several genes associated with "cell wall biogenesis," "cell wall organization," and "cell wall modification" were differentially expressed, suggesting the role of structural defense genes in FW response in chickpea similar to the observations reported from other legumes (Chang et al, 2021;Sharma et al, 2016). Several pathways related to specific physiological, metabolic, and biochemical changes were also upregulated in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Pathogen invasion is known to affect the structure and integrity of the plant cell wall. In this study, several genes associated with "cell wall biogenesis," "cell wall organization," and "cell wall modification" were differentially expressed, suggesting the role of structural defense genes in FW response in chickpea similar to the observations reported from other legumes (Chang et al, 2021;Sharma et al, 2016). Several pathways related to specific physiological, metabolic, and biochemical changes were also upregulated in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…We used the RNA seq approach to obtain the transcriptomes of MYMV infected and uninfected control of VGGRU-1 and VRM (Gg) 1. The number sequence reads from four libraries ranged from 23.2 to 25.1 million reads, and more than 80% clean high quality reads matched on the reference genome, which was similar to reported mungbean RNA-seq data [35][36][37], confirming that the sequencing depth was satisfactory for the transcriptome coverage and further data analysis. We have found 896 genes in resistant genotype and 506 genes in susceptible genotype differentially expressed between their respective infected and uninoculated control.…”
Section: Discussionsupporting
confidence: 81%
“…A number of plant defence mechanisms against Fusarium wilt have been investigated in several crops including soybean ( Lanubile et al 2015 ) and common bean ( Xue et al 2015 ). These studies have found that after infection many Fusarium resistant genotypes contain genes that contribute to R-gene mediated defence, structural defence, signal transduction and secondary metabolites ( Upasani et al 2017 ; Chen et al 2019 ) and these molecular mechanisms have also recently been confirmed in resistant mungbean genotypes ( Chang et al 2021 ). Further research is required to determine the mechanisms underpinning disease tolerance in the mungbean genotypes identified in this study.…”
Section: Discussionmentioning
confidence: 96%